A Key Metabolic Regulator of Bone and Cartilage Health - Elizabeth Pérez-Hernández; Jesús Javier Pastrana-Carballo; Fernando Gómez-Chávez; Ramesh C. Gupta; Nury Pérez-Hernández (Endocrinology and Metabolism, 2022)
Taurine, a cysteine-derived zwitterionic sulfonic acid, is a common ingredient in energy drinks and is naturally found in fish and other seafood. In humans, taurine is produced mainly in the liver, and it can also be obtained from food. In target tissues, such as the retina, heart, and skeletal muscle, it functions as an essential antioxidant, osmolyte, and antiapoptotic agent. Taurine is also involved in energy metabolism and calcium homeostasis. Taurine plays a considerable role in bone growth and development, and high-profile reports have demonstrated the importance of its metabolism for bone health. However, these reports have not been collated for more than 10 years. Therefore, this review focuses on taurine–bone interactions and covers recently discovered aspects of taurine’s effects on osteoblastogenesis, osteoclastogenesis, bone structure, and bone pathologies (e.g., osteoporosis and fracture healing), with due attention to the taurine–cartilage relationship.